The global financial cycle and capital flow episodes: A wobbly link? - Beatrice Scheubel; Livio Stracca; Cédric Tille (European Central Bank (ECB), 2019)
We add to the literature on the influence of the global financial cycle (GFC) and gyrations in capital flows. First, we build a new measure of the GFC based on a structural factor approach, which incorporates theoretical priors in its definition. This measure can also be decomposed in a price-based and quantity-based version of the GFC, which is novel in the literature. Second, we compare our measure to other common existing indicators of the GFC. Third, we estimate the influence of the fluctuations in the GFC on capital flow episodes (sudden stops, ights, retrenchments, surges) and currency crises, also testing for its stability and linearity. We find that the nexus between the GFC and capital flow episodes is generally consistent and not very wobbly. In line with theoretical priors, we find some evidence that the GFC is more important for sudden stops when it is more negative, i.e. the relationship is (mildly) convex, in keeping with a role for occasionally binding constraints, but the evidence for this feature is not strong.
Keywords: F32; F33; F36; F42; F44; 330; Capital flows; global financial cycle; push factors; structural factor analysis